Manipulation of the Ti3+/Ti4+ ratio in colored titanium dioxide and its role in photocatalytic degradation of environmental pollutants - Nawaz, R. (Elsevier B.V., 2022)
The role of the Ti3+/Ti4+ ratio in colored titanium dioxide (TiO2) for photodegradation of environmental pollutants from real wastewater samples still remains under explored. The aim of this research was to modify the Ti3+/Ti4+ ratio in colored TiO2 and investigate its role in photocatalytic degradation of phenolic compounds in real agro-industrial effluent. The Ti3+/Ti4+ ratio on the surface of colored TiO2 was easily controlled by only changing glycerol content in the synthesis media and calcination temperature. X-ray diffraction, X-ray photoelectron spectroscopy, diffuse reflectance UV-Visible spectroscopy, photoluminescence spectroscopy, and electrochemical impedance spectroscopy were used to investigate changes in structural, optical, and electronic properties of colored TiO2 with varying Ti3+/Ti4+ ratios. Increase in the Ti3+/Ti4+ ratio substantially enhance the visible light absorption and narrow the bandgap of colored TiO2. Thus, an increase in Ti3+/Ti4+ratio up to 0.134 improves electrons and holes separation and reduce their recombination. Increasing the Ti3+/Ti4+ratio above 0.134 accelerates electron-hole pair recombination. At the rise in the Ti3+/Ti4+ratio up to 0.134, the degradation efficiency of phenolic compounds from actual wastewater was found to be â¼48, which is 2.5-fold higher than that of commercial TiO2. The photocatalytic degradation efficiency reached 83 for individual model phenol in an aqueous solution. Exceeding the Ti3+/Ti4+ratio over 0.134 diminishes the photocatalytic performance down to 21 phenolic compounds degradation at the highest Ti3+/Ti4+ratio of 1.154. Â© 2022 Elsevier B.V.